99mTc-Human Serum Albumin-Nanoparticle for Sentinel Lymph Node Identification - Rizky Juwita Sugiharti; Iim Halimah; Iswahyudi Iswahyudi; Maula Eka Sriyani; Eva Maria Widyasari (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
The sentinel lymph node is the first lymph node in a lymph node basin to receive lymphatic drainage from a primary tumor. An accurate identification and characterization of sentinel lymph node is very important as it helps to decide the extension of surgery, the tumor staging, and establisment of the most adequate therapy. Technetium-99m labeled Human Serum Albumin nanoparticle (99mTc-HSA nanoparticle) was prepare as a radiopharmaceutical with particle size between 100 - 200 nmthat is used in lymphoscintigraphy technique for tracinglymphatic system and identifies the sentinel lymph node. Biodistribution study of 99mTc-HSA nanoparticle was conducted in mice to identify the accumulation of this agent in sentinel node and the other tissue. 99mTc-HSA nanoparticle showed good accumulation in sentinel node about1.29 +0.90 %ID with value of popliteal extraction 89.55 +8.52 at one hour post injection. This result was indicated that 99mTc-HSA nanoparticle is very promising compound to be further explored as sentinel lymph node imaging agent.Key words: Lymphoscintigraphy, 99mTc-HSA-nanoparticle, sentinel lymph node